INTEGRATION OF LANGUAGE AND RELIGIOUS DEVELOPMENT IN EARLY CHILDHOOD IN RA BAIT QUR'ANY - Hikmah, Nurul; Mubarok, Muhammad Naelul (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Early childhood education in Islam is an effort to optimize all the potential that exists in children, as an effort to prepare children for the tamyîz period (children can distinguish between good and bad according to Allah and the Messenger. For this reason, in the development of children's language, it is necessary to integrate with children's religious development so that the development of children's language is good in accordance with the teachings of Islam. Purpose: Based on this, this study aims to find out how to integrate early childhood language and religious development in RA Bait Qur'any. Method: This study uses an observation method with a descriptive analysis of a qualitative approach. Result: The results of this study explain that the integration of children's language and religious development can be seen in each learning theme. Conclusion: Each theme includes religious materials such as aqidah, shari'ah and morals to develop children's language skills such as reciting, listening, reading, writing and understanding by using play, conversation, stories and tours.